2020
DOI: 10.1159/000507219
|View full text |Cite
|
Sign up to set email alerts
|

Response Rate and Prognostic Impact of Salvage Chemotherapy after Nivolumab in Patients with Advanced Gastric Cancer

Abstract: Objective: Nivolumab is recommended as a third-line treatment in patients with unresectable advanced or recurrent gastric cancer. Although recent studies have demonstrated the prognostic impact of salvage chemotherapy after immune checkpoint inhibitors in several malignancies, its clinical significance remains unclear in patients with gastric cancer. This study aimed to investigate tumor response to subsequent chemotherapy after nivolumab in patients with advanced gastric cancer and assess the prognostic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…For patients with progressive disease status after ICI treatment, another therapy sometimes could be administered to extend their life. Several studies have reported that salvage chemotherapy (SCT) administered after immunotherapy would be effective for patients with metastatic non-small-cell lung cancer (NSCLC), metastatic melanoma, B cell lymphoma, advanced gastric cancer, and metastatic urothelial carcinoma [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Furthermore, SCT has been reported to be an effective treatment for HNSCC in R/M as well as other carcinomas and is attracting attention as a sequential treatment [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…For patients with progressive disease status after ICI treatment, another therapy sometimes could be administered to extend their life. Several studies have reported that salvage chemotherapy (SCT) administered after immunotherapy would be effective for patients with metastatic non-small-cell lung cancer (NSCLC), metastatic melanoma, B cell lymphoma, advanced gastric cancer, and metastatic urothelial carcinoma [ 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Furthermore, SCT has been reported to be an effective treatment for HNSCC in R/M as well as other carcinomas and is attracting attention as a sequential treatment [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, most PD-L1 antibodies prevent the interaction between PD-L1 and CD80 and between PD-L1 and PD-1, but not the interaction between PD-1 and PD-L2. Therefore, it is possible that depending on which interaction predominates in a particular cancer, PD-1 and PD-L1 antibodies may not have redundant activity (Arigami et al, 2020). Results from subgroup analysis showed that any grade pruritus and rash developed from PD-1 inhibitor were decreased FIGURE 6 | Forest plots of the relative risks and 95% CIs for pruritus and rash in comparison of combined immunotherapy and either monotherapy: (A) any grade pruritus for PD-1/-L1 plus CTLA-4 inhibitor compared to PD-1/-L1 inhibitor; (B) high grade pruritus for PD-1/-L1 plus CTLA-4 inhibitor compared to PD-1/-L1 inhibitor; (C) any grade rash for PD-1/-L1 plus CTLA-4 inhibitor compared to PD-1/-L1 inhibitor; (D) high grade rash for PD-1/-L1 plus CTLA-4 inhibitor compared to PD-1/-L1 inhibitor; (E) any grade pruritus for PD-1/-L1 plus CTLA-4 inhibitor compared to CTLA-4 inhibitor; (F) any grade rash for PD-1/-L1 plus CTLA-4 inhibitor compared to CTLA-4 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…The major physiological role of CTLA-4 seems to be through distinct effects on the two main subsets of cluster of differentiation four positive (CD4 + ) T cells: down modulation of helper T cell activity and enhancement of regulatory T (Treg) cell immunosuppressive activity ( Bylicki et al, 2020 ; Cancela et al, 2020 ; Peggs et al, 2009 ). Blockade of the PD-1 pathway may enhance antitumor immune responses by diminishing the number and/or suppressive activity of intratumoral Treg cells ( Arigami et al, 2020 ). It is thought that PD-1 predominantly regulates effector T cell activity within tissue and tumors, whereas CTLA-4 predominantly regulates T cell activation ( Arigami et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations